A cellular base station antenna configuration for variable coverage - Abdul-Rahman Shakeeb; K. H. Sayidmarie (Institute of Advanced Engineering and Science, 2019)
The field coverage offered by the base station antenna in GSM systems influences the reception and interference performances. The coverage can be varied by scanning the mainbeam direction or varying the shape of the radiation pattern. In cellular system applications, a simple technique is desirable to achieve this goal. A simple technique to vary the coverage of cellular base station is investigated. The technique uses two conventional antennas tilted by a certain angle and fed by the same signal but at variable amplitudes. It is demonstrated that the field across one half of the covered sector can be gradually increased while that at the other half is reduced by varying the excitations of the two antenna elements. This can be deployed in a simple electronic means in response to the changing scenario rather readjusting the direction of the base station antenna.